PENGARUH PEMBERIAN GLUCOMANNAN HYDROLYSATES (GMH) DAN LACTIC ACID (LA) TERHADAP PENINGKATAN JUMLAH KOLONI BAKTERI LACTOBACILLUS spp PADA BACTERIAL VAGINOSIS WANITA USIA SUBUR - Miftakhul Mahfirah Ermadona; Indah Mauludiyah (Jurnal Online Keperawatan Indonesia, 2022)
Bacterial Vaginosis (BV) is an infection caused by an imbalance in the normal vaginal flora where lactobacillus spp., producing hydrogen peroxidase (H2O2) is replaced by anaerobic bacteria such as Gardnerella vaginalis, Mobiluncus spp., Prevotella spp., Bacterides, and Mycoplasma sp., which are generally occurs in women of childbearing age (WUS). Substitution of Lactobacillus spp., this causes a decrease in H2O2 which is generally characterized by the production of a lot of vaginal secretions, gray to yellow, thin, homogeneous, has a fishy odor, and there is an increase in pH. Glucomannan Hydrolysates (GMH) as a prebiotic is expected to provide nutrition to Lactobacillus spp so that it can multiply and increase in number, while BV gel containing Lactic Acid (LA) can reduce vaginal pH to become acidic so that pathogenic bacteria are not suitable for growing in an acidic environment. The type of research used is true experiment pretest - posttest. Respondents in the study totaled 28 people and were grouped into 4, namely 1) Given metronidazole antibiotics. 2) Given Antibiotics + GMH. 3) Given LA. 4) Given LA+GMH. The number of bacterial colonies through the streak plate method. Giving LA+GMH to BV women of childbearing age has a significant effect on increasing the number of Lactobacillus spp bacterial colonies. Therefore giving LA+GMH is useful in treating BV.